AIR POLLUTION CONTROL TECHNIQUES & A CASE STUDY OF INDUSTRIAL AIR EMISSIONS - Malik, S. R.; Maqbool, M. A.; Khan, J. R. (The Nucleus, 2020)
Air pollutants are the most dangerous type of pollution and they effect our environment the worst. The main air pollutants are CO2, CO, NOx, SOx and particulate matter. These pollutants are causing some major environmental and health concerns. There are number of techniques to control these emissions to the atmosphere. The flue gas data of boilers and generators from ICI polyester industry is also included in this paper. The techniques in use to control the pollutants are discussed. One of the most common techniques is the switching of the fuel. The Natural gas emits almost 30 percent less carbon dioxide than oil, and just under 45 percent less carbon dioxide than coal. Emissions of particulates from natural gas combustion are 90 percent lower than from the combustion of oil, and 99 percent lower than burning coal. Natural gas emits virtually no sulfur dioxide, and upto 80 percent less nitrogen oxides than the combustion of coal. Similarly, use of compressed natural gas in vehicle reduces the amount of these emissions considerably. The other methods for the control and reduction of these emissions are combustion control techniques, Flue gas treatment and Fuel re-burning. NOx can be reduced considerably by combustion control techniques like Low excess air, staged air combustion, staged fuel combustion, external flue gas recirculation, Fuel induced recirculation and steam/water injection. The flue gas treatments like selective non-catalytic reduction (SNCR) and selective catalytic reduction (SCR) are also used for reduction of NOx.